No survival benefit for patients with melanoma undergoing sentinel lymph node biopsy: critical appraisal of the Multicenter Selective Lymphadenectomy Trial‐I final report. (1st March 2015) - Sladden, M.; Zagarella, S.; Popescu, C.; Bigby, M.
Summary: Background: Sentinel lymph node biopsy (SLNB) was developed in the hope that it would improve outcomes for patients with melanoma. SLNB is an area of discussion and controversy in melanoma medicine. The final trial results of the Multicenter Selective Lymphadenectomy Trial (MSLT‐I) have now been published and the authors suggest their long‐term results 'clearly validate the use of sentinel‐node biopsy in patients with intermediate‐thickness or thick primary melanomas'. An accompanying editorial states that MSLT‐I is a practice‐changing trial. Conclusions: However, critical appraisal of MSLT‐I data does not support the claims of the final report. On the contrary, MSLT‐I failed to demonstrate that there is a significant treatment‐related difference in the 10‐year melanoma‐specific survival rate in the overall study population. Furthermore, there was no improvement in overall or melanoma‐specific survival of the intermediate‐thickness group (1·2–3·5 mm). Completion lymphadenectomy can result in complications in about a third of patients, with a rate of clinically significant lymphoedema following axillary or groin dissection of 5–10%. Unnecessary lymphadenectomy can therefore have a major effect on patient quality of life. The evidence provided by Morton et al . does not support the claim that sentinel lymph node biopsy followed by lymphadenectomy in patients with positive sentinel nodes should be the standard of care in patients with melanoma. Readers are encouraged to check with registration sites to make sure declared primary outcomes are fairly reported. Post‐hoc analyses are at best exploratory and cannot be used to form the principal conclusions of a trial.